Assessment of Tariff Reform in the 1990s - Rosario G. Manasan; Rosario G. Querubin (Philippine Institute for Development Studies (PIDS), 1997)
Assessment of trade reforms in the 1990s suggests achievement of considerable progress in tariff simplification and improvement in international competitiveness. The same observation, however, cannot be claimed on reforms resulting to a uniform pattern of protection across sectors. Results from this study indicate the need for a more focused restructuring in agriculture and food processing sub-groups if the 5% uniform tariff rate is to be achieved by 2004. Addressing the problems of low productivity and poor market structure, rather than price intervention are a more viable solution in arresting the problems plaguing agriculture sector.
Keywords: 330; tariff; uniform tariff rate; effective protection rate; implicit tariff rate